Monte Carlo Simulation for Economic Analysis of Hydropower Pumped Storage Project in Nepal - Vereide, Kaspar; Lia, Leif; Ødegård, Laras (Hydro Nepal: Journal of Water, Energy and Environment, 2013)
Investments in hydropower pumped storage projects (PSP) are subjected to a high degree of uncertainty. In addition to normal uncertainties in hydropower schemes, the profit of a pumped storage scheme is dependent on the margin between power prices for buying and selling, which is difficult to predict without a power purchase agreement (PPA). A PSP without a PPA and without known construction costs requires quantification of the uncertainties in order to make qualified decisions before investing in such projects. This article demonstrates the advantages of using Monte Carlo (MC) simulations as a tool in the economic analysis of PSPs. The method has been tested on a case study, namely the Tamakoshi-3 Hydropower Project (HPP) in Nepal. The MC method is used to calculate the probability distribution of the net present value of installing reversible units in the Tamakoshi-3 HPP. The calculations show that PSPs may be profitable in Nepal, given a beneficial development of the power market. The MC method is considered to be a useful tool for economic analysis of PSPs. In this case study of installing reversible units in the Tamakoshi-3 HPP, there are many uncertainties, which the MC simulation method is able to quantify. Hydro Nepal; Journal of Water, Energy and Environment Vol. 12, 2013, January Page: 39-44 DOI: http://dx.doi.org/10.3126/hn.v12i0.9031 Uploaded Date : 10/29/2013